USE OF ARTIFICIAL INTELLIGENCE SYSTEMS AND INTELLIGENT TECHNOLOGIES IN THE ANALYSIS AND AUDIT OF THE FINANCIAL CONDITION OF A RETAIL NETWORK UNDER MARTIAL LAW AND IN UKRAINE’S POST-WAR RECOVERY - Nazarova, Karina; Ostapchuk, Zlatoslava (Current Problems of Sustainable Development, 2026)
The article explores the theoretical and applied aspects of implementing intelligent systems for analyzing and auditing the financial condition of enterprises in the retail network sector. Under the conditions of martial law and Ukraine’s future post-war recovery, traditional control methods require transformation due to high risk dynamics and environmental uncertainty. The author substantiates the concept of synergy between artificial and human intelligence, where machine learning algorithms perform mass data processing, while the specialist provides professional judgment and ethical assessment. Special attention is paid to mathematical modeling of liquidity using neural networks and regression models, which enables predictive analysis of cash flows. The essence of continuous auditing is revealed as a tool for ensuring business transparency for international investors. A separate section highlights the ethical aspects of using automated systems, particularly the principles of algorithmic explainability and auditor responsibility. The results of the study emphasize that the implementation of intelligent systems in accounting and analytical processes is a fundamental condition for building a resilient retail business and Ukraine’s successful integration into the global economic space.